Optimalisasi Potensi Sukun Sebagai Bahan Pangan Lokal dalam Mewujudkan Ketahanan Pangan Nasional - Aza Fauziana, Noer; Mila Prametha, Novika; Mardiyana, Mardiyana; Handayani, Murni (Politeknik Negeri Ketapang, 2025)
Indonesia relies heavily on rice as its main food source, but local production is insufficient, resulting in increased rice imports. Breadfruit (Artocarpus altilis) has the potential to be an alternative sustainable food source because it can grow on various types of land and can be harvested twice a year. Breadfruit has a high nutritional content, is lower in calories than rice, and is rich in minerals and vitamins. In addition, breadfruit has health benefits such as antibacterial, antifungal, and antitumor properties. However, breadfruit faces major challenges such as its short shelf life and the public's view that it is an inferior food. Breadfruit processing technology into flour can overcome these obstacles by extending the shelf life and opening up opportunities for diversifying the use of breadfruit in various food products. This article examines the potential of breadfruit as a local food ingredient to improve national food security, encourage innovation in the food industry, and provide information on the nutritional and health benefits of breadfruit. By optimizing the use of breadfruit, it is hoped that sustainable food sovereignty can be created in Indonesia.